Brain Gym and Core Stability Exercises are Superior in Improving Dynamic Balance in 8-9-Year-Old Children - Larashati, Ni Putu Dwi; Sundari, Luh Putu Ratna; Wahyuddin, Wahyuddin; Adiputra, Luh Made Indah Sri Handari; Iswari, Ida; Tianing, Ni Wayan; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 2 (2024): Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : The COVID-19 pandemic has led to low physical activity levels among children, resulting in a high risk of falls and injuries. Core stability exercises are standard practices to enhance dynamic balance. Brain Gym and balance boards are alternative activities that can be provided to children to improve dynamic balance. This study aims to demonstrate that combining Brain Gym and core stability exercises is more effective in enhancing dynamic balance in 8-9-year-old children than balance boards and core stability exercises. Methods : This study employed an experimental design using a Randomized Pre-Test and Post-Test Control Group Design involving 32 participants divided into two groups. Results : The Wilcoxon signed-rank test revealed a significant difference with a p-value of <0.01 in both Group I and Group II. The difference in means-tested by the Mann-Whitney U-test showed an essential difference between Group I and Group II with a p-value of 0.001 (p <0.05). Conclusion : Brain Gym and core stability exercises are superior in improving dynamic balance in 8-9-year-old children compared to balance boards and core stability exercises.   Keywords : Brain Gym, balance board, core stability exercise, dynamic balance